The Two Asses of Zechariah 9:9 in Matthew 21 - Instone-Brewer, David (Tyndale bulletin, 2003)
Matthew appears to depart from the Synoptics, Johannine tradition and from common sense when he gives Jesus two asses to ride on for his grand entrance into Jerusalem. Most commentators have assumed that Matthew misunderstood the meaning of the parallelism in Zechariah 9:9, which caused him to create another animal to enable Jesus to fulfil the prophecy. It will be suggested here that Matthew understood the concept of parallelism, but that he did not believe that Scripture should be interpreted in that way. This is in line with rabbinic thought of the first century which rejected the concept of parallelism in Scripture.